2016
DOI: 10.1111/bph.13409
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional crosstalk via IL‐6, PGE2and PGD2between murine myofibroblasts and alternatively activated macrophages enhances anti‐inflammatory phenotype in both cells

Abstract: BACKGROUND AND PURPOSEAlternatively activated macrophages (AAMs) are important cells in the resolution of inflammation and tissue repair. We examined the impact of myofibroblasts, a vital cell in wound healing and tissue repair, on the development and function of AAMs. EXPERIMENTAL APPROACHThe interaction between AAMs and myofibroblasts was tested using conditioned medium from murine dermal myofibroblasts and bone marrow-derived macrophages. AAMs were differentiated with IL-4 and IL-13. KEY RESULTSConditioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 69 publications
4
29
0
2
Order By: Relevance
“…A more recent study was designed to delineate the effects of myofibroblast‐derived signals on M2a macrophages; primary murine bone marrow–derived macrophages were pretreated with IL‐4 and IL‐13 to generate M2a macrophages and subsequently cultured in primary murine dermal myofibroblast‐conditioned media . The authors found that myofibroblast‐conditioned media promoted increased gene expression of M2 markers arginase 1 (ARG1) and chitinase‐3‐like 3 (YM1), along with spontaneous secretion of IL‐10 and suppressed nitric oxide production.…”
Section: Macrophage–fibroblast Crosstalk In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study was designed to delineate the effects of myofibroblast‐derived signals on M2a macrophages; primary murine bone marrow–derived macrophages were pretreated with IL‐4 and IL‐13 to generate M2a macrophages and subsequently cultured in primary murine dermal myofibroblast‐conditioned media . The authors found that myofibroblast‐conditioned media promoted increased gene expression of M2 markers arginase 1 (ARG1) and chitinase‐3‐like 3 (YM1), along with spontaneous secretion of IL‐10 and suppressed nitric oxide production.…”
Section: Macrophage–fibroblast Crosstalk In Vitromentioning
confidence: 99%
“…The authors found that myofibroblast‐conditioned media promoted increased gene expression of M2 markers arginase 1 (ARG1) and chitinase‐3‐like 3 (YM1), along with spontaneous secretion of IL‐10 and suppressed nitric oxide production. To understand the downstream effects of this behavioral shift in the macrophages, myofibroblasts were then cultured in conditioned media derived from the M2a macrophages that had been cultured with myofibroblast‐derived signals, which resulted in reduced migration, expression of COX2, and production of PGE2 and PGD2 . These results suggest that M2a macrophages cultured with myofibroblast‐conditioned media may in turn be able to inhibit downstream myofibroblast behavior in another feedback loop .…”
Section: Macrophage–fibroblast Crosstalk In Vitromentioning
confidence: 99%
“…Indeed, IL‐10 and Arg1 have both been implicated in the prevention of tissue damage as well as in the regulation of pathological tissue remodeling in settings of type 2 immunity . Thus, the PG‐driven induction of these regulatory factors may provide a negative feedback loop, which limits further activation and migration of myofibroblasts during physiological tissue repair . This implicates PGE 2 in the transition from the inflammatory to the proliferative phase of tissue repair and in the prevention of aberrant (myo)fibroblast activation.…”
Section: Roles Of Eicosanoids In Tissue Repairmentioning
confidence: 99%
“…[45][46][47] Thus, the PG-driven induction of these regulatory factors may provide a negative feedback loop, which limits further activation and migration of myofibroblasts during physiological tissue repair. 48 This implicates PGE 2 in the transition from the inflammatory to the proliferative phase of tissue repair and in the prevention of aberrant (myo)fibroblast activation. Due to its regulatory effects on fibroblasts, PGE 2 also functions as an important negative regulator of pulmonary fibrosis and airway remodeling in asthma.…”
Section: Prostaglandin E 2 -A Key Eicosanoid In Physiological Tissue mentioning
confidence: 99%
“…Fibroblasts are abundant in the heart and have multiple potential roles during myocardial inflammation and repair that follows MI (Porter & Turner 2009). In addition to the production of collagen and other matrix proteins that determine scar integrity, they secrete molecules, including cyto­kines, prostaglandins (Shinde & Frangogiannis 2014, Fernando et al 2015, Turner 2016) and microRNA (Fang & Yeh 2015), capable of regulating inflammation (Porter & Turner 2009, Chen & Frangogiannis 2013, van Nieuwenhoven & Turner 2013), Treg recruitment (Frangogiannis 2014), angiogenesis (Newman et al 2011), cardiogenesis (Furtado et al 2014) and hypertrophy (Abonnenc et al 2013, Cartledge et al 2015). The role of cardiac fibroblast 11β-HSD1 in regulating the cellular secretome and on the response to MI and other pathological challenges merits further investigation.…”
Section: β-Hsd1 MI and Heart Failurementioning
confidence: 99%